2019
DOI: 10.1038/s41598-018-37841-8
|View full text |Cite
|
Sign up to set email alerts
|

Operation mode of a step-feed anoxic/oxic process with distribution of carbon source from anaerobic zone on nutrient removal and microbial properties

Abstract: This study investigated the operation mode of a step-feed anoxic/oxic (A/O) process with distribution of the carbon source from the anaerobic zone in terms of the treatment effects on sewage with low carbon and high nitrogen and phosphorus. After seven phases of operation, an optimal flow distribution ratio of 75%:25% was obtained from the anaerobic zone, and the concentrations of chemical oxygen demand, ammonia nitrogen, total nitrogen, and total phosphorous in the effluent were 20.8, 0.64, 14.2, and 0.89 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…The identified denitrifiers belonged to phyla Acidobacteria, Actinobacteria Bacteroidetes, Chloroflexi, Proteobacteria (Table S2). These five main phyla from this study are consistent with the work of Shen et al [19]. They found these same phyla in full-scale domestic WWTPs (step-feed and anoxic/aerobic process).…”
Section: Effects Of Cod:n Ratios On Populations Of Dnbsupporting
confidence: 92%
See 1 more Smart Citation
“…The identified denitrifiers belonged to phyla Acidobacteria, Actinobacteria Bacteroidetes, Chloroflexi, Proteobacteria (Table S2). These five main phyla from this study are consistent with the work of Shen et al [19]. They found these same phyla in full-scale domestic WWTPs (step-feed and anoxic/aerobic process).…”
Section: Effects Of Cod:n Ratios On Populations Of Dnbsupporting
confidence: 92%
“…AOB species included Nitrosomonas europaea, Nitrosomonas halophile, Nitrosospira multiformis, Nitrosospira tenuis and Zoogloea caeni via 16S rRNA of CTO primer pairs and Nitrosoccus halophilus via 16S rRNA of EUB primer pairs (see Table S2). Moreover, AOB communities present in this study were similar to those found by Shen et al [19], who investigated the microbial community in a full-scale domestic WWTP (anoxic/oxic process). The main AOA communities at SF 1 were Crenarchaeotal sp.…”
Section: Microbial Communities By Using Qpcr and Dgge Technique Aob And Archaea (Aoa) Populations And Communitiessupporting
confidence: 87%
“…Some common biological treatment methods are aerobic, anaerobic, anoxic, and facultative processes, bioremediation, phytoremediation, and mycoremediation [ 35 , 36 ]. Aerobic treatment methods include activated sludge, trickling filters, rotating biological contactors, and oxidation ponds, which require oxygen for the breakdown of organic matter for wastewater treatment [ 37 ]. Anaerobic treatment methods use anaerobic digesters and up-flow anaerobic sludge blanket reactors, that operate in the absence of oxygen to treat wastewater and leads to methane production [ 29 ].…”
Section: Description Of Conventional Methods For Wastewater Treatmentmentioning
confidence: 99%
“…The disadvantages lie in the large land area required and a long retention time, especially for aerobic treatment. These methods are sensitive to temperature, pH, toxicity, and shock loads, which can affect the performance and stability of the biological process [ 37 ]. Anaerobic treatment can produce excess sludge with odor problems, requiring further treatment prior to disposal.…”
Section: Description Of Conventional Methods For Wastewater Treatmentmentioning
confidence: 99%
“…On this basis, some improvements were made to the AAO process to improve the efficiency of wastewater treatment. Using an internal reflux system in the deoxidation zone, a step-feed AAO process for treating low-carbon and highnitrogen wastewater by distributing carbon sources from the anaerobic zone has been developed to improve the treatment response [13]. To reduce the carbon source requirement, the practicability of mixing free acid sludge treatment and dissolved oxygen (DO) management to achieve partial nitrification-denitrification in a continuous flow system (an aerobic-anoxic-oxic process) using real wastewater was assessed [14].…”
Section: Introductionmentioning
confidence: 99%